Surgical Endodontic Parameters in the Mandibular Premolars Area: An Anatomic Evaluation with Cone -Beam Computed Tomography - Jabbari Moghadam , Pouya; Sanei, Maryam (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: This study aimed to evaluate the relationship between mandibular premolars and the surrounding critical anatomical structures for endodontic surgery using cone-beam computed tomography (CBCT). Materials and Methods: In this cross sectional study, 170 CBCT images were evaluated in the sagittal, coronal, and axial planes to measure the buccal bone thickness (BBT) covering each root, the diameter of the premolars in the buccolingual and mesiodistal dimensions, besides the total amount of tissue needed to be resected for endodontic surgery; these measurements were performed at the 3mm level of the apex. Also, the distances from the superior border of mental foramen (MF) to premolars apex and alveolar crest (AC) were measured. Moreover, the position of MF in relation to adjacent teeth was evaluated. Descriptive statistics, independent-sample T-test and Wilcoxon test were used in the SPSS 26 to analysis of the data (α=.05). Results: The mean values of BBT for the first and second premolars were measured 1.18 mm and 1.57 mm, respectively. The root diameters of the first and second premolars were measured 4.02 mm and 3.98 mm in the buccolingual dimension, and 2.74 mm and 2.98 mm in the mesiodistal dimension. The total amount of tissue needed to be resected for endodontic surgery in the second premolar has a higher amount with a mean of 5.55 mm. The second premolar was recorded as the tooth with the closest root apex to MF with a mean value of 3.97 mm. The mean distance between MF and AC was measured 13.88 mm, and MFs in most cases (44.11 %) were positioned in line with the second premolar long axis. Conclusion: According to findings of the present study, the CBCT imaging evaluation is recommended for each patient before the surgical endodontic operation.